HIGH TECHNOLOGYIN THE AGE OFSCIENTIFICAND TECHNOLOGICALREVOLUTION(social-philosophical analysis) - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
The article is devoted to the specificity of the high technologies’ development in the epoch of scientific-technological revolution.